A Study on Burden of Prehypertension in Youth (or Pediatric Hypertension) in West Bengal, India - RoyChoudhury, Sourav; Nayek, Kaustav; Saha, Jinia (Journal of Child Science, 2021)
Hypertension is a silent threat to the developing countries in recent times. The aim of this article was to determine the burden of prehypertension and hypertension among school-going children and the risk factors associated with those conditions. A cross-sectional study was conducted among school-going children (6–18 years) in seven schools of Burdwan, West Bengal, India, selected by stratified random sampling from March 2017 to August 2018. Anthropometric and blood pressure measurements were obtained along with sociodemographic parameters. Prehypertension and hypertension were defined as per American Pediatric Society's definition. Mean age of the study population was 11.3 ± 3.8 years (n = 604). Prevalence of prehypertension and hypertension was estimated to be 5% and 4.6%, respectively. Both prehypertension and hypertension were more common among children aged > 15 years (10.3% and 15.5%). In logistic regression, the independent determinants of hypertension were higher socioeconomic condition, increasing age, obesity, increased intake of junk food, parental hypertension, and obesity among first-degree relatives. Proper preventive measures are the need of the hour to tackle the emerging epidemic at its root. Periodic measurements of blood pressure at regular intervals are advisable at community levels to recognize high-risk children, control obesity, and prevent irreversible end organ damages.
Keywords: obesity; hypertension; community; pre-hypertension; systolic hypertension; children